Stability analysis of Takagi–Sugeno systems using a switched fuzzy Lyapunov function - Elias, Leandro J.; Faria, Flávio A. [UNESP]; Araujo, Rayza; Oliveira, Vilma A. (Elsevier, 2021)
In this paper, a switched fuzzy Lyapunov function approach is proposed to analyze the stability of continuous-time Takagi–Sugeno fuzzy systems. The results are established by exploring properties of the membership functions. The key point is that the time derivatives of the membership functions are represented as a finite polytope and less conservative linear matrix inequalities are obtained. Numerical examples illustrate the efficiency of the new stabilizing conditions.
Keywords: Domain of attraction estimates; Finite polytopic representation; Linear matrix inequalities; Switched fuzzy Lyapunov functions; Takagi–Sugeno systems